PERSONNEL MARKETING AS AN ELEMENT OF INNOVATIVE DEVELOPMENT OF AGRICULTURAL ENTERPRISES - MANKO, Stanislav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the essence and significance of personnel marketing as an integral component of the innovative development of agricultural enterprises. It substantiates the theoretical and practical aspects of integrating marketing principles into the human resource management system of agrarian organizations under modern conditions of digitalization and sustainable development. The study emphasizes that personnel marketing acts as a strategic tool for attracting, developing, and retaining qualified employees, forming a positive employer brand, and fostering innovative behavior among staff. It is argued that the effective implementation of HR marketing contributes to strengthening the competitiveness of agricultural enterprises, enhancing corporate culture, and ensuring a balance between economic efficiency, social responsibility, and environmental safety. Special attention is paid to the connection between personnel marketing and the concept of sustainable development, which encompasses economic, social, and ecological components. The paper identifies the key stages of implementing an innovative development model for agricultural enterprises, highlighting the growing importance of artificial intelligence technologies, precision farming, and digital communication tools. The communication function of personnel marketing is considered a crucial factor in shaping internal and external interactions, improving motivation, and building trust between employers and employees. Based on the analysis of scientific literature and current practices, the article proposes practical recommendations aimed at increasing the effectiveness of HR marketing in agricultural enterprises. These include developing an HR-marketing strategy aligned with the company’s innovation policy, implementing employer branding focused on stability and technological advancement, expanding the use of digital platforms for recruitment and employee engagement, and investing in staff training in automation and data management. The obtained results can serve as a basis for further research on digital models of HR marketing and the formation of innovative human capital in the agrarian sector.